Conservative treatment of stage III lung cancer using chemoradiotherapy in hypofractionation mode, case report - N. V. Marinichenko; K. K. Laktionov; A. V. Nazarenko; T. N. Borisova; M. S. Ardzinba; A. A. Fedorova; P. V. Murashova; M. S. Ardzinba (Медицинский совет, 2020)
Lung cancer is a leader in the world in terms of morbidity and mortality. Moreover, the number of patients with locally advanced forms of non-small cell lung cancer exceeds 30% of all newly diagnosed cases. The standard of treatment for patients with inoperable stage III lung cancer is chemoradiotherapy. Currently, ways to increase the effectiveness of chemoradiotherapy are being considered, in particular, local escalation of the radiation dose to the tumor, which allows personalizing approaches in the treatment of this category of patients. One of the most common complications of chemoradiotherapy is post-radiation pulmonitis, which requires timely diagnosis and treatment with glucocorticosteroids in severe cases. We present a case report of a patient with locally advanced non-small cell lung cancer who received treatment as part of simultaneous chemoradiotherapy in the hypofraction mode, complicated by post-radiation pulmonitis. Successful treatment of complications led to the restoration of the general condition of the patient; during the follow-up examination, a complete response to the specific treatment was recorded. Thus, a promising method of treating patients with inoperable stage III non-small cell lung cancer is the option of simultaneous chemoradiotherapy with local escalation of the radiation dose to the tumor, while being wary of complications such as pulmonitis, allows for timely diagnosis and treatment of the condition.